EXPLORING CONCEPTIONS OF DISORDERS AND DISABILITY, MENTAL HEALTH PROBLEMS, PSYCHOSOCIAL DISABILITY AND MENTAL DISORDER: A REVIEW OF THE LITERATURE - Nardith Johanna Vega Pipa (DIALÉCTICA, 2025)
In Colombia, during and after the COVID-19 pandemic, some children and adolescents presented symptoms that impacted their mental health. An increase in the levels of anxiety, depression, stress, among others, was observed. Although these symptoms can manifest themselves in different ways, it is crucial to differentiate their classification: mental health problems (or diseases), mental disorders and psychosocial disability. To this end, entities such as the World Health Organization (WHO) and the American Psychiatric Association (APA) have developed criteria to categorize these disorders. Although these constructs originate in the health sector, their incidence in education has generated great challenges when thinking about quality education, which has led to the need to transcend from medical models focused on rehabilitation to social and rights-based models that promote values of inclusion and equity, but has also created terminological ambiguities that hinder the conceptual distinction between mental health problems, mental disorders and psychosocial disability, which perpetuate homogenizing practices, attitudinal barriers and social stigmas. Therefore, the main objective of this research is to establish a conceptual distinction between these categories, using a descriptive-exploratory methodology based on the review of academic literature. Documents from international entities that classify developmental disorders and national policies related to the participation of people with diagnoses were included, in addition to searches in databases such as Google Scholar, Scielo, Dialnet and Scopus. Research on higher education and those that do not explicitly address the conceptualization of the terms analyzed were excluded. The findings highlight the importance of providing support that addresses the particularities of each individual. It is concluded that a clear and precise understanding of these concepts is essential to move towards inclusive and rights-based practices.